Perioperative safety determinants in ethnic patient groups. Issue 1 (February 2023) - Bloo, Gerrit; Calsbeek, Hiske; Westert, Gert; Dekkers, Wim; Akkersdijk, George; Krugten, Robbert Jan van; Wolff, André P; Wollersheim, Hub
Background: In a Dutch hospital, unexpectedly, safer perioperative care was found in non-western ethnic minority patients compared to Dutch ethnic majority patients undergoing high-risk surgery with a mortality risk >1%. We explored determinants in order to find tools for nurses and physicians to improve patients' safety and safety experience during the perioperative period. Methods: A qualitative grounded theory design was applied to understand patients' perspective on their needs and safety in the perioperative period we interviewed patients ( n = 17). Results: Three themes emerged: 'Nurse & physician behaviour', 'Team performance', and 'Patient behaviour'. In the first theme 'Nurse and physicians' behaviour', positive determinants related to an attitude of experienced professionals that provide patients with trust. On the other hand, negative determinants provide patients with experiences of unsafety. In the second theme 'Team performance', positive determinants involved effective communication and coordinated care of the nurses and physicians. Negative determinants related to visible disagreement about the treatment. In the third theme 'Patient behaviour', positive determinants related to seeking support from nurses, physicians, and family to recover and to endure an anxious period. Negative determinants related to missing appointments or not consulting the information provided. Conclusion and practice implications: 'Nurse & physician behaviour' and 'Team performance' are relevant determinants that contribute to patients' experiences of safe care. Stimulating an active attitude of patients in seeking support may contribute to experiences of safe care. These results can be used to improve patients' experience of safe care in an uncertain and vulnerable perioperative period.